2004
DOI: 10.1162/1088198041269472
|View full text |Cite
|
Sign up to set email alerts
|

Applying Ecological Input‐Output Flow Analysis to Material Flows in Industrial Systems: Part II: Flow Metrics

Abstract: This article, continuing with the themes of the companion article, expounds the capabilities of input‐output techniques as applied to material flows in industrial systems. Material flows are the primary focus because of their role in directly linking natural and industrial systems and thereby being fundamental components of environmental issues in industrial economies. The specific topic in this article concerns several material flow metrics used to characterize system behavior that are derived from the ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…As formalized later in this study, the potential uncertainty of a system increases with its number of flows and decreases when more and better data are incorporated. graph-theoretical applications draw from theoretical ecology (Odum 1994;Ulanowicz 1997) and analogies between ecosystems and social, economic, and industrial systems have been identified (Côté and Hall 1995;Graedel 1996;Korhonen 2001;Bailey et al 2004). As reviewed in Schiller and colleagues (2014), graph-theoretical network measures have been applied for describing system structures in IE and for comparing different systems to one another (for a recent application, see Nuss et al [2016]).…”
Section: Uncertainty In Materials Flow Analysismentioning
confidence: 99%
“…As formalized later in this study, the potential uncertainty of a system increases with its number of flows and decreases when more and better data are incorporated. graph-theoretical applications draw from theoretical ecology (Odum 1994;Ulanowicz 1997) and analogies between ecosystems and social, economic, and industrial systems have been identified (Côté and Hall 1995;Graedel 1996;Korhonen 2001;Bailey et al 2004). As reviewed in Schiller and colleagues (2014), graph-theoretical network measures have been applied for describing system structures in IE and for comparing different systems to one another (for a recent application, see Nuss et al [2016]).…”
Section: Uncertainty In Materials Flow Analysismentioning
confidence: 99%
“…In an extension of this Johnson et al [38] discuss energy flows in stainless steel production and the effect of recycling on this while Schmidt [39] well-known Sankey diagrams to material and energy flows. Bailey et al [40] discuss briefly the limitations of these methodologies which may all be attributed to such detail material properties, qualities etc. not being included.…”
Section: Environmental Accountingmentioning
confidence: 99%
“…Second and more specifically, ecology and input-output analysis have borrowed from each other with the former adopting portions of the mathematical framework developed in the latter. 7 More recently, Bailey and colleagues have taken the adaptation of ecological input-output analysis and re-applied it to industrial systems (Bailey et al 2004a(Bailey et al , 2004b. Suh (2005) argues that input-output analysis as used in ecology and economics have much in common in their model formulation, but that they look systems from opposite directions: ecologists start from the input side (nutrient and energy inputs) and economists start from the output side (final demand).…”
Section: The Biological Analogymentioning
confidence: 99%
“…In contrast, substance flow analysis, while in principal not incompatible with input-output analysis, has not made use of IO analysis as extensively. For two examples, however, see the study by (Konijn et al 1997) on iron steel and zinc and the study of aluminum by Bailey (Bailey et al 2004b) who also provides a useful and more detailed account of the intersections between MFA and input-output analysis.…”
Section: Energy and Materials Flow And Io Analysismentioning
confidence: 99%